Competences of management accounting systems in managing environmental costs of listed companies in sri lanka - Indrani, M.W.; Naidoo, M.; Wickremasinghe, G. (International Journal of Accounting & Business Finance, 2020)
This study explores the way and the extent to which listed companies in Sri Lanka manage environmental costs through their management accounting (MA) systems.Applying Mixed Method Research approach; data were collected from 42 listed companies representing five industry sectors in Sri Lanka, through a survey followed by discussions with financial executives and environmental officers of companies. Further, it reviewed National Environmental Act of Sri Lanka for legislation enacted for sampled companies. The main tools of analysis were frequency tables for quantitative data, and qualitative data were analyzed linking them with quantitative analysis and, thus providing expressive detailed interpretations for the phenomena under investigations. Findings indicate that even though all companies are bounded by legislation to take environmental management (EM) initiatives to prevent and control pollution, the MA systems of most companies have not been improved accordingly to incorporate environmental costs and related performance measures. All companies used to take EM measures by making adjustments to existing financial accounting/MA systems which were initiated mainly to facilitate regular business activities. These practices thus, demonstrate lower potential for companies in managing EM costs. Competencies of MA techniques considered differ one to another in managing EM costs, showing greater importance for traditional MA techniques like budgeting, products costing than modern MA techniques like kaizen costing, balanced scorecards. Conversely, the Plantation sector shows greater ability in managing environmental costs through their activity based costing systems implemented by all in the sector. It suggests companies to establish appropriate accounting systems and performance measures which are capable of identifying and managing environmental costs precisely. It also suggests improving awareness among all personnel including accounting staff on how to manage environmental costs through such systems ensuring legal compliances, profitability and survival of the business.
Keywords: MA systems; MA techniques; Environmental costs; Listed companies; Industry sectors